Formulation of Sodium Valproate Nanospanlastics as a Promising Approach for Drug Repurposing in the Treatment of Androgenic Alopecia - Farid. A. Badria; Hassan A. Fayed; Amira K. Ibraheem; Ahmed F. State; Eman A. Mazyed (MDPI AG, 2020)
Sodium valproate (SV) is an antiepileptic drug that is widely used in the treatment of different seizure disorders. The topical SV has a hair regenerative potential through activating the Wnt/β-catenin pathway and anagen phase induction. The aim of the current investigation was to fabricate nanospanlastics of SV for improving its dermal delivery by providing prolonged drug effect and increasing its permeability for treatment of androgenic alopecia (AGA). SV-loaded nanospanlastics were formulated according to 23 factorial design by ethanol injection method using a non-ionic surfactant (Span 60) and edge activators (EAs), such as Tween 80 and Cremophor RH 40, to explore the influence of different independent variables on entrapment efficiency (EE%) and percentage drug released after 12 h (Q12h) in order to choose the optimized formula using Design-Expert software. The optimized formula (F8) appeared as spherical deformable vesicles with EE% of 90.32 ± 2.18% and Q12h of 90.27 ± 1.98%. F8 exhibited significant improvement of ex vivo permeation than free SV. The clinical study exhibited no comparable difference between F8 and marketed minoxidil lotion. However, F8 demonstrates less adverse effects than minoxidil lotion. Nanospanlastics could be a safe and effective method for improving the topical delivery of SV in the management of AGA.